1986
DOI: 10.1017/s0022215100099692
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphohexose isomerase levels in patients with head and neck cancer

Abstract: Serum phosphohexose isomerase (PHI) levels were estimated in 28 patients with head and neck cancer. The mean value was significantly higher when compared to the controls. There was no difference in mean PHI value with respect to the character of the lesion or with the histopathological type of growth. The activity was increased with the advancement of the stage of cancer.With radiotherapy, a gradual and significant decrease in serum PHI activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Goel et al (1986) had similar results. On comparing serum PHI levels according to the histological type of cancer it was observed in present study ( Table V) that most of patients (86%) studied had squamous cell carcinoma.…”
Section: Observationssupporting
confidence: 61%
See 2 more Smart Citations
“…Goel et al (1986) had similar results. On comparing serum PHI levels according to the histological type of cancer it was observed in present study ( Table V) that most of patients (86%) studied had squamous cell carcinoma.…”
Section: Observationssupporting
confidence: 61%
“…A significant rise in serum PHI level was found in lymphoepithelioma as compared to other histological types. Goel et al (1986) did not observed any significant alteration in PHI level in relation to the histology of the tumor.…”
Section: Observationsmentioning
confidence: 58%
See 1 more Smart Citation
“…Thus, a reliable TAA, rapidly and accurately reflecting the efficacy of treatment, would be of considerable value in the management of such patients. Moreover, all clinically applica ble TAA were rather disappointing in head and neck squamous cell carcinoma [1][2][3]. SCC Ag is a TAA which was firstly de scribed by Kato and Torigoe [4] and Kato et al [5] in patients with cervical squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although various substances have been evaluated as indicators of tumor pres ence in untreated patients, such as CEA, ferri tin or phosphohexose isomerase, none of these substances has proven to be clinically useful [1][2][3]. In 1977 Kato and Torigoe [4] isolated an antigen from squamous cell carci noma of the cervix with an apparent molecu lar mass of 48 kD, called tumor antigen Ta-4.…”
Section: Introductionmentioning
confidence: 99%